Developing big ocean system in support of Sustainable Development Goals: challenges and countermeasures. Issue 4 (26th November 2021) - Zhang, Bin; Li, Fuchao; Zheng, Gang; Wang, Yanjun; Tan, Zhetao; Li, Xiaofeng
ABSTRACT: The ocean is a critical part of the global ecosystem. The marine ecosystem balance is crucial for human survival and sustainable development. However, due to the impacts of global climate change and human activities, the ocean is rapidly changing, which poses an enormous threat to human health and the economy. "Conserve and sustainably use the oceans, seas and marine resources" is one of the 17 Sustainable Development Goals (SDGs). Therefore, it is urgent to construct a transformative marine scientific solution to promote sustainable development. Marine data is the basis of ocean cognition and governance. Marine science has ushered in the era of big data with continuous advances in modern marine data acquisition. While big data provides a large amount of data for SDG research, it simultaneously brings unprecedented challenges. This study introduces an overall framework of a system for solving the current problems faced by marine data serving SDGs from the perspective of marine data management and application. Also, it articulates how the system helps the SDGs through two application cases of managing fragmented marine data and developing global climate change data products.